Toward an index to assess transitions from emergency response to rebuilding livelihoods - Hauser, Michael; Mugonya, John (International Food Policy Research Institute, 2021)
Safety net programs generally employ thresholds (using a set benchmark of assets, income, or a timeline) to graduate beneficiaries off program support (Browne 2013; Sabates-Wheeler and Devereux 2011). However, many participants in short-term programs fall back to preprogram vulnerability and poverty levels within a short time (Sabates-Wheeler and Devereux 2011), suggesting that threshold-based graduation is an inappropriate way to determine the capability of participants to leave the program. Thus, the concept of “sustainable graduation” has been put forward to better assess the ability of a household to withstand shocks without damaging losses (Sabates-Wheeler and Devereux 2013).